Corporate Governance, Profitabilitas, dan Nilai Perusahaan - Syamsul Bakhtiar; Hijroh Rokhayati (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this study was to analyze the effect of corporate governance on firm value, analyze the effect of profitability on firm value, and analyze the effect of mediating profitability on the relationship between corporate governance and firm value. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2020. The sampling technique uses a purposive sampling method with the criteria for companies listed on the Indonesia Stock Exchange and annual reports available on the company's official website. The sample of this research is a company that is included in the consumer goods industry sector, totaling 50 companies. The data source in this study is secondary data obtained from the IDX website and the company's official website. The data analysis technique in this study used the Partial Least Square (PLS) SEM method with the help of SmartPLS 3.0 software. The results of the study show that corporate governance has a significant positive effect on firm value. Meanwhile, corporate governance has no significant effect on company profitability, and profitability has no significant effect on firm value. Profitability is not able to mediate the relationship between the influence of corporate governance on firm value.